2004
DOI: 10.1111/j.1742-6723.2004.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between bicarbonate measured on arterial and venous blood gases

Abstract: Venous bicarbonate estimation shows a high level of agreement with the arterial value, with acceptably narrow 95% limits of agreement. These results suggest that venous bicarbonate estimation may be an acceptable substitute for arterial measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 10 publications
5
30
2
4
Order By: Relevance
“…Nonetheless, that the patient population in the study had a predominance of patients with sepsis does limit the generalizability of our results, especially in patients with very low cardiac output. Third, the study did use central venous samples obtained from a central line, not peripheral venous samples; however, given that our study found acceptable agreement between arterial and central venous values, it would be expected that similar agreement would be found if peripheral venous samples were used, which in fact has been confirmed by both our own results and those of other studies (7)(8)(9)(10)(12)(13)(14)(15) …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nonetheless, that the patient population in the study had a predominance of patients with sepsis does limit the generalizability of our results, especially in patients with very low cardiac output. Third, the study did use central venous samples obtained from a central line, not peripheral venous samples; however, given that our study found acceptable agreement between arterial and central venous values, it would be expected that similar agreement would be found if peripheral venous samples were used, which in fact has been confirmed by both our own results and those of other studies (7)(8)(9)(10)(12)(13)(14)(15) …”
Section: Discussionsupporting
confidence: 79%
“…A number of studies have suggested that there is agreement between ABG and VBG values, although most of the previous studies were limited by specific patient group samples (e.g., patients with diabetic ketoacidosis), analysis of only one or some parameters rather than all commonly used parameters (e.g., pH, Pco 2 , and bicarbonate), or examination of only one ABG and VBG sample per patient (7)(8)(9)(10)(11)(12)(13)(14)(15). A few authors even expressed doubts about the use of VBG values in lieu of arterial values (4 -6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although the pH and bicarbonate of venous blood have been shown to correlate well with the pH and bicarbonate of arterial blood, and may be used to identify patients with extreme hypercarbia, an arterial blood sample is necessary for assessing oxygenation and monitoring ventilation. [7][8][9] Although clinical practice guidelines suggest that blood color and pulsatile blood flow can verify a successful arterial puncture, those are subjective indicators, whereas sampler filling time is an objective indicator and may be more reliable in clinical practice. Lower blood pressures increased sampler filling times, and the longest average filling time was 20.5 s with a mean arterial pressure of 57 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…These theoretical reasons in themselves amount to approximately 2.0 mmol/L difference between calculated and measured bicarbonate. [10][11][12] The first step in assessing agreement between measured and calculated bicarbonate by correlation coefficient showed a good correlation with r = 0.950 with p < 0.05. The correlation coefficient to assess the agreement depends not only on the correlation coefficient, but also on the range of values, so a wide range of values will show a good correlation even if the values are in poor agreement.…”
Section: Discussionmentioning
confidence: 99%